Effectiveness of Health Promotion to Community-Based Total Sanitation Outcomes in Nunsaen, Kupang, Indonesia - Salesman, Frans (Jurnal Studi Komunikasi, 2018)
The Community-Based Total Sanitation Program has reached 94.95% of villages in Indonesia. However, not all villages implement the four pillars of community-based total sanitation, including the village of Nunsaen. The low outcomes of community-based total sanitation in Nunsaen village in 2016 reached 76% of 542, impacting on average 63% of the population, who suffer from infectious diseases every year. The non-implementation of health promotion strategies through advocacy, and lack of empowerment of working groups to improve community-based total sanitation outcomes in Nunsaen village. A retrospective study with Case Control approach with triggers through advocacy and empowerment to a sample of 134 family heads. Health promotion strategies through effective advocacy affect community-based total sanitation outcomes (Pvalue = 0,0001; and OR = 8,444), meaning that the effectiveness of advocacy effects is more than three times as likely to improve community-based sanitation outcomes by 8.44 times than if advocacy conducted less than three times. If in terms of OR scale, the effectiveness of community empowerment has greater opportunity (OR = 46,943) than advocacy (OR = 8,444) towards the total community-based sanitation outcome in Nunsaen village. The conclusion are Improving the effectiveness of community-based sanitation implementation requires advocacy and community empowerment by types and techniques determined by the program to achieve healthy and hygienic behavioural changes as the goal of community-based sanitation programs.